An Introduction to Law - Phil Harris (Cambridge University Press, 2007)
Since the publication of its first edition, this textbook has become the definitive student introduction to the subject. As with earlier editions, the seventh edition gives a clear understanding of fundamental legal concepts and their importance within society. In addition, this book addresses the ways in which rules and the structures of law respond to and impact upon changes in economic and political life. The title has been extensively updated and explores recent high profile developments such as the Civil Partnership Act 2005 and the Racial and Religious Hatred Bill. This introductory text covers a wide range of topics in a clear, sensible fashion giving full context to each. For this reason An Introduction to Law is ideal for all students of law, be they undergraduate law students, those studying law as part of a mixed degree, or students on social sciences courses which offer law options.